Food-Derived Hemorphins Cross Intestinal and Blood–Brain Barriers In Vitro - Domenger, Dorothée; Cudennec, Benoit; Kouach, Mostafa; Touche, Véronique; Landry, Christophe; Lesage, Jean; Gosselet, Fabien; Lestavel, Sophie; Goossens, Jean-François; Dhulster, Pascal; Ravallec, Rozenn (Frontiers in Endocrinology, 2018)
A qualitative study is presented where the main question was whether food-derived hemorphins, i.e. originating from digested alimentary hemoglobin, could pass the intestinal barrier and/or the blood-brain barrier (BBB). Once absorbed, hemorphins are opioid receptor (OR) ligands that may interact with peripheral and central OR and have effects on food intake and energy balance regulation. LLVV-YPWT (LLVV-H4), LVV-H4, VV-H4, VV-YPWTQRF (VV-H7) and VV-H7 hemorphins that were previously identified in the 120 min digest resulting from the simulated gastrointestinal digestion of hemoglobin have been synthesized to be tested in in vitro models of passage of IB and BBB. LC-MS/MS analyses yielded that all hemorphins, except the LLVV-H4 sequence, were able to cross intact the human intestinal epithelium model with Caco-2 cells within 5 to 60 min when applied at 5 mM. Moreover, all hemorphins crossed intact the human BBB model with brain-like endothelial cells (BLEC) within 30 min when applied at 100 µM. Fragments of these hemorphins were also detected, especially the YPWT common tetrapeptide that retains OR-binding capacity. A cAMP assay performed in Caco-2 cells indicates that tested hemorphins behave as OR agonists in these cells by reducing cAMP production. We further provide preliminary results regarding the effects of hemorphins on tight junction proteins, specifically here the claudin-4 that is involved in paracellular permeability. All hemorphins at 100 µM, except the LLVV-H4 peptide, significantly decreased claudin-4 mRNA levels in the Caco-2 intestinal model. This in vitro study is a first step towards demonstrating food-derived hemorphins bioavailability which is in line with the growing body of evidence supporting physiological functions for food-derived peptides.